Curricula in Teaching Classification and Indexing in Advanced Courses in Library and Information Science:A Case Study - Gopinath, M. A. (Journal of Information and Knowledge, 1999)
Presents the structure of Curriculum of three advanced courses in the library and information science, focusing on the classification and indexing language area. While contents of these courses are same in respect to knowledge and skills to be imparted, they are varied in distribution into papers with different marks tally. However, the teaching tutorials and project work in three schools have built into their frame the design and development of vocabulary control devices such as classification, thesaurus and index and their applications to practical information resource systems.